Similar Device Architectures for Inverted Organic Solar Cell and Laminated Solid-State Dye-Sensitized Solar Cells. (14th July 2012) - Khatri, Ishwor; Bao, Jianfeng; Kishi, Naoki; Soga, Tetsuo
Abstract : Here, we examine the device architecture of two different types of solar cells mainly inverted organic solar cells and solid state dye-sensitized solar cells (DSSCs) that use organic materials as hole transportation. The inverted organic solar cells structure is dominated by work on titanium dioxide (TiO 2 ) and zinc oxide (ZnO). These layers are sensitized with dye in solid state DSSCs. Because of the similar device architecture, it becomes possible to fabricate laminated solid-state DSSCs. The performance of the device was improved by varying the top metal electrode. In laminated solid-state DSSC, we expect that excited dye molecules inject electron into the conduction band of nanocrystallineTiO 2 layer, whereas P3HT provides efficient hole transportation. These solar cells are promising for future energy source as they are cheaper, light weight, flexible and made into large areas, which are showing growing importance.